Have you Read This? An Empirical Comparison of the British REF Peer Review and the Italian VQR Bibliometric Algorithm. (14th May 2021) - Checchi, Daniele; Ciolfi, Alberto; De Fraja, Gianni; Mazzotta, Irene; Verzillo, Stefano
Abstract : This paper determines the assessment of publications submitted to the UK research evaluation carried out in 2014, the REF, which would have resulted if they had been assessed with the bibliometric algorithm used by the Italian evaluation agency, ANVUR, for its evaluation of the research of Italian universities. We find extremely high correlations between the two assessment approaches.